Evaluation of the effect of titanium dioxide nanoparticles on the shear bond strength of orthodontic bonding agent and composite adhesive - Akel, Nimat E. Al (My University, 2022)
Amaç: Bu araştırmanın amacı, TiO2-NP ortodontik bonding ajanı ve kompozit yapıştırıcının makaslama bağlanma kuvveti üzerindeki etkisini değerlendirmektir. Gereç ve Yöntem: Bu çalışmada, ortodontik bonding ajanı ve TiO2-NP ile entegre ortodontik kompozit yapıştırıcının makaslama bağlanma kuvvetini değerlendirmek amacıyla Marmara Üniversitesi Diş Hekimliği Fakültesi Cerrahi ndan 60 adet çekilmiş sağlam premolar diş kullanılmıştır. Grup A'da, braket uygulaması için bonding ajanına TiO2-NP ilave edilmiştir. Grup B'de, braket uygulaması için kompozit yapıştırıcıya TiO2-NP ilave edilmiştir. Grup C, normal bonding ajanı ve adeziv kompozit ile braket uygulaması yapılan dişleri içermiştir. Deney sonrası, tüm grupların makaslama bağlanma kuvveti, Evrensel Çekme Dayanımı test cihazı kullanılarak ölçülmüştür. Bulgular: bonding ajanına TiO2-NP eklenmesinin braket-diş arayüzünün kesme bağlanma mukavemeti üzerinde önemli bir etkisinin olmadığı bulundu. Ayrıca, ortodontik kompozit adeziv içine TiO2-NP'nin dahil edilmesinin, kesme bağlanma mukavemeti üzerinde minimum etkiye sahip olduğu bulundu. Sonuç: TiO2-NP'ler, ortodontik tedavi sırasında braket yapışmasının kesme bağlanma mukavemetinden ödün vermeden WSL'ler umut verici bir antibakteriyel ajandır.

Aim: Evaluation of the shear bond strength of orthodontic bonding agent and orthodontic composite adhesive upon the incorporation of TiO2-NP. Materials and Methods: A total of 60 intact extracted premolar teeth were gathered from Marmara University, Department of Oral and Maxillofacial Surgery, to evaluate the SBS of orthodontic bonding agent and orthodontic composite adhesive integrated with TiO2-NP. The teeth were divided into 3 groups, Group A, B, and C. In Group A, TiO2-NP was incorporated to the bonding agent used for orthodontic bracket application. In Group B, TiO2-NP were incorporated to the composite adhesive. Group C would contain teeth that underwent orthodontic bracket application with normal bonding agent and adhesive composite. Post- experimentation, the SBS of all groups were measured using the Universal Tensile Strength tester. Results: According to the findings, the incorporation of TiO2-NP into orthodontic bonding agent had no significant effect on the shear bond strength of the bracket- tooth interface. It was also found that incorporating the TiO2-NP into the orthodontic composite adhesive had minimal effect on the shear bond strength. Conclusion: TiO2-NPs is a promising antibacterial agent preventing WSLs during orthodontic treatment without compromising the shear bond strength of the bracket adhesion.
Keywords: Health; Makaslama bağlanma dayanımı; Nanoparticles; Nanopartiküller; Orthodontic Titanium Dioxide; Orthodontic Treatment; Orthodontics; Ortodonti; Ortodontik tedavi; Sağlık; Shear bond strength; Titanyum dioksit